Spaces of effort, exploration of an experience of mobility. Issue 1 (2nd January 2017) - Bahrami, Farzaneh; Rigal, Alexandre
Abstract: This article combines empirical, theoretical, and philosophical references to explore the notion of Effort as an integral part of active mobility and urban experience. Considering the increasing value of physical effort in urban life styles, we challenge the general premise of transport planning that tends to reduce the effort required for mobility – particularly when providing alternatives to car use. Informed by interviews we have conducted with inhabitants of three major agglomerations in Switzerland, Zurich, Geneva, and Lausanne, we identify a threefold approach to effort, and explore the spatial implications of them for urban spaces that contribute to the practice of active mobility. We introduce the notion of entraining effort, as engaging and stimulating experience that improves the actor's qualifications and result in the development of skills that facilitate making more effort. We take examples of existing urban spaces that effectively accommodate varied physical activities, and encourage entraining effort, underlining these spaces' fragmentary character and that they are rarely part of the daily urban commute. We conclude that in order to effectively move toward prevalence of active mobility, engaging and integrating the exerted effort in daily commutes; these spaces need to form an ensemble – providing accessibility throughout the city.